Staging the Arctic 1819–1909 and 2014 - Hansson, Heidi (Nordlit, 2015)
Throughout the long nineteenth century and beyond, outside representations of the Arctic on stage have circulated a stereotypical image of the region. The two most long-standing emblems are ice and indigenous culture, and as commodity, the Arctic is identified as mystical, authentic, natural and pre-modern. These images are circulated in popular, cultural events like theatre performances, panoramic displays, music hall shows, and musical comedy but their presence in a popular cultural context also contributes to destabilise the signifiers. At the best, theatre productions about the Arctic may produce a kind of history from below, including a cautious critique of the colonial project and the ideal of heroic masculinity. Their radical potential should not be overstated, however, since the historical meanings of the stereotypes even when they are being debunked. At least on stage, conventional images of the Arctic continue to dominate.